AB0291C REMISSION IN RHEUMATOID ARTHRITIS: CONSIDERING NEW CUT-POINTS OF COMPOSITE DISEASE ACTIVITY INDICES ACCORDING TO THE ABSENCE OF SYNOVITIS BY ULTRASONOGRAPHY. (June 2019) - Bertoli, Ana; Audisio, Marcelo; Benegas, Mariana; Bravo, Maximiliano; Catay, Erika; Cazenave, Tomás; Hartvig, Claudia; Kohan, Paula; Marin, Josefina; Martire, Victoria; Navarta, David; Rosa, Javier; et al.
Abstract : Background: Achieving the state of remission in RA according to currently available criteria does not entirely prevent patient from radiological progression. On the contrary, the presence of subclinical synovitis by means of ultrasonography (US) correlates with radiological progression. Objectives: To stablish cut-off values of composite disease activity indices (DAS28-CRP, DAS28-ESR, CDAI and SDAI) that adjust better to remission according to the absence of synovitis by US. Methods: Observational, cross-sectional study that included 126 patients with diagnosis of RA who were in remission or low disease activity (DAS-ESR ≤3.2). For each patient we calculated the DAS28-ESR, DAS28-CRP, CDAI, SDAI. For US assessment we used the 12 joint simplified score. We considered the state of remission by US if synovial hypertrophy (SH) ≤1 and power Doppler (PD) signal= 0 in all joints. The cut-off values of the disease activity indices to define remission according the proposed US definition of remission were determined by ROC curves. Results: Patients had a median (ICR) DAS28-ESR of 2.32 (0.60), DAS28-CRP= 1.89 (0.55), CDAI= 3.56 (3.0) and SDAI= 3.0 (4.7). The sensitivity, specificity, positive and negative predictive value of each of the selected cut-off points for the DAS28-CRP, DAS28-ESR, CDAI and SDAI for the definition of remission are shown in the Table. Conclusion: In this study we describe new cut points of the different composite disease activity indices for the definition of remission. These cut points improve the accuracy of the definition of remission. However, they differ scarcely from the reference values making its impact uncertain in the long term management of patients with RA. Longitudinal studies are, therefore, warranted in order to elucidate the performance of these new cut points. Reference: [1] Aletaha D, Smolen JS. Clin Exp Rheumatol2006; 24(6Suppl 43): S-45-51. Disclosure of Interests: None declared